De kracht van de gekleurde bril: Implicaties van religieus pluralisme op de levensovertuiging van gelovigen, atheïsten en spirituelen - Pons-de Wit, Anneke (Religie & Samenleving, 2020)
It is a mainstay in the sociology of religion that the reflexivity that appears in religious pluralist societies has an impact on the religious identity of individuals. According to Peter Berger, reflexivity replaces the certainty of the taken-for-granted worldview by enduring uncertainty, hence relativizing every religious identity. However, his theory is underdeveloped concerning the role of culture. He fails to describe how worldviews not just respond to the pressure to relativize, but are already involved in the definition, interpretation, and integration of reflexivity itself. The aim of this article is to study the role of the worldview in dealing with reflexivity more thoroughly. A comparison between the religious trajectories of religious, atheist, and spiritual individuals, demonstrates that their own worldview restricts the scope of reflexivity letting it ending up in purification instead of relativization of religious identities.